The Reflection of the Active School Ideas in Didactical Views of J. Laužikas - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 1991)
Jonas Laužikas (1903-1980), in his works, focused on studying foreign pedagogical thought. He was well aware of the pedagogical currents of the end of 19th century and beginning of the 20th century (work, school activities, action, experimental, personality, pragmatist, aesthetic education, existentialist and others. pedagogical currents), with practical experience foreign teachers. Particular attention Laužikas devoted to the new German school, whose theory and practical experience he had very thoroughly studied and had found valuable things there. However, it should be noted that Laužikas was quite critical of all theories (both traditional and new) and practice, showing not only positive but also negative aspects and mistakes made. Critical analysis of new ideas was assisted by a great knowledge of the history of pedagogy. Laužikas dealt with almost every educational problem, especially issues of personalization and differentiation of training, activeness of the students, from the historical point of view, trying to show historical origins and evolution of the issues discussed.